2004
DOI: 10.1038/nrm1499
|View full text |Cite
|
Sign up to set email alerts
|

The LIM domain: from the cytoskeleton to the nucleus

Abstract: First described 15 years ago as a cysteine-rich sequence that was common to a small group of homeodomain transcription factors, the LIM domain is now recognized as a tandem zinc-finger structure that functions as a modular protein-binding interface. LIM domains are present in many proteins that have diverse cellular roles as regulators of gene expression, cytoarchitecture, cell adhesion, cell motility and signal transduction. An emerging theme is that LIM proteins might function as biosensors that mediate comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
695
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 679 publications
(711 citation statements)
references
References 118 publications
12
695
2
2
Order By: Relevance
“…Given the presence of an LIM domain emerging as a hallmark of proteins that can associate with both the actincytoskeleton and the transcriptional machinery (Labouesse and Georges-Labouesse, 2003;Kadrmas and Beckerle, 2004), we started our functional characterization on ZNF185 by investigating its intracellular localization. We did not observe a significant localization of either ectopically expressed or endogenous ZNF185 within the nucleus, but instead found that ZNF185 is an actin-cytoskeleton-associated protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the presence of an LIM domain emerging as a hallmark of proteins that can associate with both the actincytoskeleton and the transcriptional machinery (Labouesse and Georges-Labouesse, 2003;Kadrmas and Beckerle, 2004), we started our functional characterization on ZNF185 by investigating its intracellular localization. We did not observe a significant localization of either ectopically expressed or endogenous ZNF185 within the nucleus, but instead found that ZNF185 is an actin-cytoskeleton-associated protein.…”
Section: Discussionmentioning
confidence: 99%
“…The LIM domain is a cysteine-and histidine-rich double zinc-finger motif named after the three-homeodomain proteins: Lin-l 1, Isl-1 and Mec-3 (Way and Chalfie, 1988;Freyd et al, 1990;Karlsson et al, 1990). This domain is present in a wide range of proteins whose functions include many fundamental biological processes such as cell lineage specification, cytoskeleton organization and organ development (Dawid et al, 1998;Bach, 2000;Kadrmas and Beckerle, 2004). In addition, some LIM domain-containing proteins are also involved in pathological processes such as oncogenesis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose dehydrogenase Recent work has shown that zyxin also shuttles through the nucleus -most likely by association with other LIM proteins -and may regulate gene transcription (Nix et al, 2001;Wang and Gilmore, 2003;Kadrmas and Beckerle, 2004). During mitosis, a fraction of zyxin becomes associated with the tumour suppressor h-warts at the mitotic apparatus (Hirota et al, 2000).…”
Section: -3-3mentioning
confidence: 99%
“…The LIM domain is a double zinc-fingers in structure and was initially identified in Caenorhabditis elegans Lin-11, rat Isl-1 and C. elegans Mec-3, from which the acronym LIM was derived. 14,15 The LIM protein family can be subdivided into different subfamilies according to sequence homology within the LIM domains, the number of LIM domains and their organization within the proteins. Ajuba belongs to Zyxin/Ajuba subfamily, including Zyxin, Ajuba, Trip6, Wtip, Limd1 and Lpp.…”
mentioning
confidence: 99%